Benign Mesenchymal Odontogenic Tumor: Cemento-Ossifying Fibroma - Sridevi, Ugrappa; Jain, Ajay (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Fibro-osseous lesions are a heterogeneous group of benign lesions of unknown etiology affecting the jaws and other craniofacial bones, which are characterized by the replacement of normal bone by fibrous tissue, which contains a newly formed, mineralized product. The origin of cemento-ossifying fibroma is not clearly understood and have been categorized under various sub-groups. These most ill-defined and confusing lesions are categorized under “benign mesenchymal odontogenic tumours”. It is considered as relatively most rare, benign, slow growing, non-odontogenic intra bony neoplasm.